FORMULASI DAN EVALUASI SABUN CAIR EKSTRAK ETANOL JAHE MERAH (Zingiber officinale var Rubrum) SERTA UJI AKTIVITASNYA SEBAGAI ANTIKEPUTIHAN - Mutmainah Mutmainah; Yuvianti Dwi Franyoto (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2015)
ABSTRACT Fluor albus is a genital disorder symptoms by women because of infections caused by bacteria, viruses, fungi or parasites. Red ginger (Zingiber officinale var Rubrum) is one of the natural ingredients has been used the potential as antifungal because of the content the active compound for example flavonoids, alkaloids, tannin, saponin and terpenoid. In this research, examines the effects of antifungal C. albicans ethanol extract red ginger after formulated vaginal douche with varying concentrations of 10%, 15% and 20%. vaginal douche is made using by soap base sodium lauryl sulfate, citric acid, sodium chloride, propilenglikol and water. Red ginger extraction methods remaserasi for 5 days using ethanol 96% by the turn of the solvent every 24 hours. Test power using the antifungal C. albicans on PDA medium. Evaluation of vaginal douche red ginger extract consist of organoleptic, homogenity, specific of gravity, pH, and antifungal effect. The results showed that the concentration of ethanol extract red ginger 10%, 15% and 20% have antifungal activity against C. albicans. Power test vaginal douche red ginger activity lower than vaginal douche containing povidone iodine as an active ingredient with the analysis results were significantly different (p <0.05). Keywords: Vaginal douche, Red ginger, C. albicans.